The practice of international health a case-based orientation - Perlman, Daniel, 1950-; Roy, Ananya (New York ; Oxford : Oxford University Press, 2009)
This book comprises a series of first person accounts in which physicians, epidemiologists, health workers, and public health professionals from around the world present the critical dilemmas and challenges facing the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: World health -- Case studies